Influence of inflammation and nitric oxide upon platelet aggregation following deposition of diesel exhaust particles in the airways. (27th May 2017) - Smyth, E; Solomon, A; Birrell, M A; Smallwood, M J; Winyard, P G; Tetley, T D; Emerson, M
Abstract : Background and Purpose: Exposure to nanoparticulate pollution has been implicated in platelet‐driven thrombotic events such as myocardial infarction. Inflammation and impairment of NO bioavailability have been proposed as potential causative mechanisms. It is unclear, however, whether airways exposure to combustion‐derived nanoparticles such as diesel exhaust particles (DEP) or carbon black (CB) can augment platelet aggregation in vivo and the underlying mechanisms remain undefined. We aimed to investigate the effects of acute lung exposure to DEP and CB on platelet activation and the associated role of inflammation and endothelial‐derived NO. Experimental Approach: DEP and CB were intratracheally instilled into wild‐type (WT) and eNOS −/− mice and platelet aggregation was assessed in vivo using an established model of radio‐labelled platelet thromboembolism. The underlying mechanisms were investigated by measuring inflammatory markers, NO metabolites and light transmission aggregometry. Key Results: Platelet aggregation in vivo was significantly enhanced in WT and eNOS −/− mice following acute airways exposure to DEP but not CB. CB exposure, but not DEP, was associated with significant increases in pulmonary neutrophils and IL‐6 levels in the bronchoalveolar lavage fluid and plasma of WT mice. Neither DEP nor CB affected plasma nitrate/nitrite concentration and DEP‐induced human platelet aggregation was inhibited by an NO donor. Conclusions and Implications: Pulmonary exposure to DEP and subsequent platelet activation may contribute to the reports of increased cardiovascular risk, associated with exposure to airborne pollution, independent of its effects on inflammation or NO bioavailability.